2012
DOI: 10.1371/journal.pone.0029258
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Ultrastructure of Bone Based on Electron Microscopy of Ion-Milled Sections

Abstract: The relationship between the mineral component of bone and associated collagen has been a matter of continued dispute. We use transmission electron microscopy (TEM) of cryogenically ion milled sections of fully-mineralized cortical bone to study the spatial and topological relationship between mineral and collagen. We observe that hydroxyapatite (HA) occurs largely as elongated plate-like structures which are external to and oriented parallel to the collagen fibrils. Dark field images suggest that the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
199
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(218 citation statements)
references
References 42 publications
16
199
1
2
Order By: Relevance
“…9). This observation is in good agreement with densities measured experimentally46, 47, 48 and supports the idea that bone tissue nanostructure has evolved in order to be strong yet lightweight to facilitate movement and mobility 3…”
Section: Resultssupporting
confidence: 89%
“…9). This observation is in good agreement with densities measured experimentally46, 47, 48 and supports the idea that bone tissue nanostructure has evolved in order to be strong yet lightweight to facilitate movement and mobility 3…”
Section: Resultssupporting
confidence: 89%
“…A recent study using ion-milled cryogenic femoral bone found consistent platelet sizes of 5 nm thick, 70 nm wide, and >200 nm long. (53) The platelets may be arranged in stacks, (1) so that several are placed side by side in a particular gap channel, or extending between fibrils across a series of gap channels. (15) Although their long axes align with that of the adjacent collagen fibril, the planes of stacks around and between fibrils may not be similar; there is some evidence that they vary significantly across local areas.…”
Section: Mineral Plateletsmentioning
confidence: 99%
“…The deposited calcium phosphate is subsequently converted into hydroxyapatite (HA) [Ca 10 (PO 4 ) 6 (OH) 2 ] in specific areas of the extracellular matrix (ECM). Various experiments have revealed the presence of HA crystals both inside and outside collagen fibrils in the ECM (McNally et al 2012) and also within the lumen of matrix vesicles (MVs) (Ali et al 1970;Anderson 1969;Bonucci 1970). MVs are extracellular vesicles with a diameter ranging from approximately 100 to 300 nm (Anderson 2003;Anderson et al 2010;Cui et al 2016;Golub 2009;Wuthier and Lipscomb 2011) which harbor the biochemical machinery needed to establish the appropriate inorganic pyrophosphate (PP i ) to inorganic phosphate (P i ) ratio (Ciancaglini et al 2006Harmey et al 2004;Hessle et al 2002;Johnson et al 2000;Roberts et al 2007;Yadav et al 2011;Zhou et al 2012) required to initiate the synthesis of apatitic mineral (Bechkoff et al 2008;Thouverey et al 2009;Wu et al 1997), which will subsequently be propagated onto the collagenous ECM.…”
Section: Mineralization Process and The Biogenesis Of Matrix Vesiclesmentioning
confidence: 99%
“…It has been proposed that the pattern of holes and overlap sites among collagen molecules provide channels or gaps in their assemblage where HA crystals can nucleate (Landis et al 1993). However, the majority of bone mineral is external to the collagen fibers (McNally et al 2012;Pidaparti et al 1996). In contrast with the well-documented events explaining collagen-mediated mineralization, it has been hard to visualize how apatite crystals from MVs could make their way to the collagen fibrils and help to promote further mineral propagation.…”
Section: The Role Of Phosphatases In Mv-mediated Initiation Of Skeletmentioning
confidence: 99%
See 1 more Smart Citation